Patents and traditional knowledge: facing biopiracy - Klocke, Julia (Centre for Law and Society, 2026)
Humankind has always been dependent on Earth and its biological diversity.1 For generations, humans have passed on their knowledge about life, livelihood, nature and biological resources, and relied upon biodiversity for many commercial products.2 Today, biodiversity is recognised as a 'highly strategic resource with commercial potential comparable to that of petroleum or uranium'. 3 The biotechnology sector 4 has emerged as a major industry in recent years. The possibility of altering living material to develop new kinds of medication and agricultural products is worth billions of dollars. 5 Companies around the world have expanded their study of the natural world and rely upon the knowledge and guidance of local communities who have profound knowledge of these biological resources. Scientists believe that the cure for diseases lies hidden in the 'green gold' of the Southern hemisphere.6 Consequently, the economic value of these biological resources is regarded as very high. In fact, commerce involving biological products and processes now accounts for almost half of the world economy.